2002
DOI: 10.1128/mcb.22.3.704-723.2002
|View full text |Cite
|
Sign up to set email alerts
|

Murine De Novo Methyltransferase Dnmt3a Demonstrates Strand Asymmetry and Site Preference in the Methylation of DNA In Vitro

Abstract: CpG methylation is involved in a wide range of biological processes in vertebrates as well as in plants and fungi. To date, three enzymes, Dnmt1, Dnmt3a, and Dnmt3b, are known to have DNA methyltransferase activity in mouse and human. It has been proposed that de novo methylation observed in early embryos is predominantly carried out by the Dnmt3a and Dnmt3b methyltransferases, while Dntm1 is believed to be responsible for maintaining the established methylation patterns upon replication. Analysis of the sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 40 publications
8
52
1
Order By: Relevance
“…DNMT1 may therefore not be the only enzyme required to maintain methylation of CpG-rich regions, as both DNMT3a and -3b3 were still largely present after drug treatment. As indicated by the hemimethylation data, DNMT3a and -3b, which are presumably targeted to CpG-rich regions, may function to randomly methylate hemimethylated molecules generated by zebularine (26), whereas, in CpG-poor regions, there are more hemimethylated molecules than fully methylated molecules throughout the period of zebularine treatment, suggesting that perhaps these regions are basically maintained by DNMT1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1 may therefore not be the only enzyme required to maintain methylation of CpG-rich regions, as both DNMT3a and -3b3 were still largely present after drug treatment. As indicated by the hemimethylation data, DNMT3a and -3b, which are presumably targeted to CpG-rich regions, may function to randomly methylate hemimethylated molecules generated by zebularine (26), whereas, in CpG-poor regions, there are more hemimethylated molecules than fully methylated molecules throughout the period of zebularine treatment, suggesting that perhaps these regions are basically maintained by DNMT1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hsieh (10) found that the cloned EBNA region of the Epstein-Barr virus genome on the episome was a better substrate for Dnmt3a than the control luciferase coding region, suggesting that there is a substrate preference for the enzyme regardless of its chromosomal location or structure. In fact, it has been demonstrated that purified Dnmt3a protein has a DNA sequence preference when either a plasmid or an oligonucleotide is used as the methylation substrate in vitro (11,12).In the present study, we attempted to identify the genomic DNA loci that are preferentially methylated by Dnmt3a or Dnmt3b in vivo. This was initially accomplished using methylation-sensitive restriction fingerprinting (MSRF), 2 which has been successfully utilized for the identification of differentially methylated genes in cancer cells (13) or during ES cell differentiation (14).…”
mentioning
confidence: 99%
“…In addition, Hsieh (10) found that the cloned EBNA region of the Epstein-Barr virus genome on the episome was a better substrate for Dnmt3a than the control luciferase coding region, suggesting that there is a substrate preference for the enzyme regardless of its chromosomal location or structure. In fact, it has been demonstrated that purified Dnmt3a protein has a DNA sequence preference when either a plasmid or an oligonucleotide is used as the methylation substrate in vitro (11,12).…”
mentioning
confidence: 99%
“…In vitro experiments indicated the differences in the preferred target sequences of these enzymes [70,71]. An inhibitor of Dnmt1, 5-Aza-deoxycytidine induces global demethylation of the genome as expected; however, locus-specific demethylation and methylation is observed [72].…”
Section: Combinations Of Dnmts and Factors Recognizing Epigenetic Infmentioning
confidence: 99%